Analisis Komponen Aktif Cita-Rasa Pada Susu Fermentasi Dengan Kromatografi Gas - Dzarnisa Dzarnisa; Herawati Latif (Agricultural Faculty, 2014)
(Active component analysis of fermented milk flavor by gas chromatography)ABSTRACT. Fermented milk is milk processed product that to be one source of nutritious food for humans. The action of food component such as flavor is accepted, sense of taste and smell generated complex assessment of food flavors in the mouth. The flavor components of fermented milk together and interact with each other when consumed and cause the perception of taste between like or dislike. This is an important factor in developing diversification of fermented milk product so as to attract customers other than in terms of aspects of nutrition and health. Flavor is one of the most important criteria in the acceptance of a food ingredient. During processing and storage flavor change easily. This study used gas chromatography to detect the formation of the active component of the flavor of fermented milk. The purpose of this study was to determine the active components in fermented milk which is the formation of flavor. This research was conducted in the Laboratory of Animal Feed Laboratory of the Faculty of Agriculture and Food Chemistry Unsyiah and PAU Food and Nutrition IPB Bogor. This study uses a Likens - Nickerson distillation stage concentrated with Vigreux column and identified by Gas Chromatography Mass Spectrometer. Gas chromatography has identified that the class of acids, alcohols, esters and alkanes group forming an active component in the flavor of fermented milk although relatively varied. In yoghurt, acid found in relatively high amount of alcohol is more varied in its kind. Yogurt with single culture L.bulgaricus has more ketones and aldehydes components. Volatile components were detected mostly in kefir acids, alcohols, esters and alkane derivatives. The curd is dominated by acidic components in addition to alcohol and aldehyde.